Intimate Partnership Formation and Intergenerational Relationships among Ethnic Minority Youth in Denmark - Singla, Rashmi (Outlines. Critical Practice Studies, 2006)
This article is based on a research project drawing upon in-depth qualitative interviews (N=61) and data from a survey (N=628) of young people and parents belonging to the five largest ethnic minority groups in Denmark. The theoretical framework combines conceptualisations about conflict and the family with theories about modernisation/individualisation and discrimination effects. The dominating tendencies in the inter-generational relationships between young people and their parents on the subject of the young people’s intimate partnership formation are analysed and discussed. The ethic minority youth and parents’ reflections on the ethnic majority partnership formation patterns are delineated. The analyses indicate that relationships between young people and parents on the issue of intimate partnership formation can be cooperative or in opposition. This is contrary to the widespread discourse about serious conflicts between generations. Thus the article criticises the reductionistic conception of partnership formation being a question of either-or processes, i.e. own choice or parental choice, and appeals for broad concepts which include both-and processes, i.e. own choice and parental accept.